Socioeconomic Determinants of Labor Informality in the Department of Puno, Peru - Ticona-Carrizales, Lucio; Portillo, Henry Amiel Condori; Rodríguez-Limachi, Omar Moisés; Incacutipa-Limachi, Duverly Joao; Yapuchura-Saico, Cristóbal Rufino; Huayta-Flores, Lenin; Ticona-Campos, Varanny Nelyda (Journal of Ecohumanism, 2024)
Labor informality is a phenomenon that impacts the economic and social development of various regions, including the department of Puno, by limiting access to labor rights and perpetuating poverty and inequality. This study aims to determine the socioeconomic factors that influence labor informality in the department of Puno. To achieve this objective, a methodology with a quantitative approach of explanatory scope and a non-experimental cross-sectional design was used, analyzing data from the National Household Survey (ENAHO) of the National Institute of Statistics and Informatics (INEI), whose sample was made up by 1,771 individuals of working age from the department of Puno. The results revealed that factors such as sex (p = 0.0470), educational level (p = 0.0000), age (p = 0.0000), area of ​​residence (p = 0.0040), financial inclusion (p = 0.0000), the type of employer occupation (p = 0.0290), the type of contract (p = 0.0000), the monthly income (p = 0.0000), the size of the company (p = 0.0010) and the type of commercial economic activity (p = 0.0000) were determining factors of labor informality. In conclusion, it is established that socioeconomic factors significantly influenced labor informality in the department of Puno, which implies that public policies should focus on improving access to education and financial services to promote the formalization of employment and, therefore, improve the living conditions of the working population.